PERSONAL INCOME TAX AND OUTPUT VOLATILITY: EMPIRICAL EVIDANCE FROM BULGARIA (Revista Inclusiones, 2021)
This article studies the influence of personal income tax in Bulgaria under business cycle. Withquarterly data of Eurostat and National Statistical Institute of Bulgaria for the period 1995-2020, theHodrick-Prescott filter, correlations and regression model between the output gap and the changesin the trend shares and the cyclical shares of personal income tax revenue in GDP, in this paper iscompare the cyclical impact of the progressive and the proportional income taxes. Proportionalincome tax replaced progressive income tax in 2008. The research examined two periods of personalincome tax revenue. The first period covered March 1995 through December 2007 with 36observations. The second period covered March 2008 through March 2020 with 49 observations. Thefirst period examined the progressive income tax. The second period examined the proportionalincome tax. The research results show that automatic changes in proportional income tax revenueare countercyclical in period of deflation and procyclical in period of inflation. The discretionarychanges in proportional income tax revenue are procyclical in period of inflation and deflation.Automatic changes in progressive income tax revenue are countercyclical in period of inflation anddeflation. The discretionary changes in progressive income tax revenue are countercyclical in periodof deflation and procyclical in period of inflation. It may be inferred that discretion and au